Innovative force sensor for indoor climbing holds - real-time measurements and data processing, design and validation - Maffiodo, D.; Sesana, R.; Gabetti, S.; Colombo, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
In this article, a system to measure the evolution of load in time and space during indoor climbing is described. The system is based on a set of dedicated multiaxial load cells, which measure the load on each hold of an indoor climbing wall. When the climber hangs on a hold, the load signal is read and sent to a digital acquisition and processing system. Sensor design allows for measurement of the force components applied to the climbing holds, regardless of the application point of the force on the hold. Local deformations were measured through strain gauges. Based on the electrical configuration of the strain gauges, the values of the applied forces can be computed, making the contributions to the deformation due to bending moments and torsion negligible. The sensor was designed, assuming a maximum applicable load of 200 kg without plastic deformation. The design process was based on both analytical and finite element method analyses. An experimental calibration and testing campaign was performed to validate the sensor design.